Sunteți pe pagina 1din 5

The Logarithm and Exponential Functions

We begin with the following question: If a > 0, what is ax ? We define

a1 = a, a2 = a · a, a3 = a · a · a, ...

and more generally,


an = |a · a{z· · · a}
n times

for positive integers n. We also define

1
a0 = 1 and a−n = for n in N.
an
1
To define ax for rational x, we first let a n be the unique b > 0 such that bn = a. This b is the nth root of a

and is also denoted by n a. It is the image of the inverse function of

f (x) = xn for all x ≥ 0

at the point a. It can also be obtained directly from the Completeness Axiom as

sup{x ≥ 0| xn < a}.

Then we define
m 1 1 m m 1
a n = (am ) n = a n and a− n = m
an
for every natural numbers m, n. Thus ax is defined for every rational number x.

The following index laws hold for every rational numbers x and y:
y
ax+y = ax · ay and axy = (ax ) .

Can we define ax for irrational numbers x so that the above index laws still hold? For example, what

should be a 2 ? One approach is to interpolate a nice curve through the points (x, ax ), for all rational
numbers x, and define ax for irrational numbers x according to the values on the curve. We observe that if
the function f : R → R satisfies

f (x + y) = f (x)f (y) for every x, y in Q, (∗)

and that f (1) 6= 0, then f (x) = f (1)x for every rational number x.

Proof: Note that f (0) = f (0 + 0) = f (0)2 so that f (0) = 0 or 1. If f (0) = 0, then

f (x) = f (x + 0) = f (x)f (0) = 0

for every x. In particular, f (1) = 0. Hence f (0) = 1. For every positive integer n,

f (n) = f (1 + · · · + 1) = f (1) · · · f (1) = f (1)n .

and 1 = f (0) = f (n + (−n)) = f (n)f (−n) so that

1 1
f (−n) = = = f (1)−n .
f (n) f (1)n

1
 n   1
As f n1 =f 1
n + ··· + 1
n = f (1), we have f 1
n = f (1) n . Finally, it is straightforward to prove that
m
 m
f n = f (1) n .

Hence we have to find a solution of (∗) such that f (1) = a. If such an f is further assumed to be
differentiable, then
f (x + h) − f (x) f (x)(f (h) − 1)
f ′ (x) = lim = lim = cf (x),
h→0 h h→0 h
for c = f ′ (0). In other words, f is a solution of the differential equation

f ′ (x) = cf (x) for every x.

It turns out that it is easier to find the inverse function g = f −1 . Intuitively, g = loga , as loga y is the
unique x such that ax = y. Now g = f −1 is also differentiable and

1 1 1
g ′ (y) = = = .
f ′ (g(y)) cf (g(y)) cy

As g(1) = 0,
Z y Z y
1 1
g(y) = g(y) − g(1) = g ′ (t) dt = dt.
1 c 1 t
When c = 1, we get the natural logarithm function, log, given by
Z x
1
log x = dt for every x > 0.
1 t

It is clear that if x < 1,


Z x Z 1
1 1
log x = dt = − dt < 0,
1 t x t
log 1 = 0, and log x > 0 if x > 1. Furthermore we have

i. log is differentiable and log′ x = 1/x;

ii. log is strictly increasing and is hence injective;

iii. log xy = log x + log y;

iv. log(x/y) = log x − log y;

v. log xn = n log x for every integer n.

Proof:

iii. Fix any y > 0 and define h(x) = log(xy). The function h is differentiable, and

1 1
h′ (x) = y log′ (xy) = y · = = log′ x.
xy x

Hence log(xy) = h(x) = log x + c for some constant c. Putting x = 1, we get c = log y and the result
follows.

2
iv. It follows from the equations
 
x x
log x = log ·y = log + log y.
y y

v. It can be proved by Mathematical Induction that

log xn = n log x for every natural number n.

It also follows from (iv) that


 n
−n 1 1
log x = log = n log = −n log x.
x x

To recover f = g −1 , note that

lim log x = +∞ and lim log x = −∞.


x→+∞ x→0+

Proof: Observe that


log 2n = n log 2, log 2−n = −n log 2, where log 2 > 0.

Hence the image of log (which is the domain of f ) is R. Let exp = log−1 . It is called the exponential
function and is defined on R into the set of all positive numbers. We have the following properties:

i. exp is differentiable and exp′ x = exp x;


ii. exp is strictly increasing;

iii. exp (x + y) = exp x · exp y.

Proof:
i. For all number x,

1 1
exp′ x = (log−1 )′ x = = = log−1 x = exp x.
log′ (log−1 x) 1/ log−1 x

iii. Suppose u = exp x and v = exp y. Then

x + y = log u + log v = log uv.

This means
exp(x + y) = uv = exp x exp y.

Re 1
Let e = exp 1. Then e is characterized by 1 t
dt = 1. As
Z 2
1
dt < 1 · (2 − 1) = 1,
1 t

and
Z 4
1 1 1 1 13
dt > · (2 − 1) + · (2 − 1) + · (2 − 1) = ,
1 t 2 3 4 12

3
we get 2 < e < 4. By some more delicate computation, we can show that e ≈ 2.71828.

From property (iii) above,


exp x = (exp 1)x = ex .

for every rational number x. Define ex = exp x for every x ∈ R. It follows that ex+y = ex · ey for every
x, y ∈ R.

In order to define ax , observe that if a > 0, then

ax = (elog a )x = ex log a ,

for every rational number x. As ex log a is defined for all x, we can use it to define ax .

Definition: If a > 0, define for every real number x,

ax = ex log a .

Note that the requirement a > 0 is necessary in order that log a is defined. The following properties
holds:

i. ax is differentiable and (ax )′ = ax log a;

ii. ax is strictly increasing;


y
iii. axy = (ax ) ;

iv. a1 = a;

v. ax+y = ax · ay .

Proof:

i. Recall that ax = ex log a . Hence by the Chain Rule,

(ax )′ = log a · ex log a = log a · ax .

iii.
x log a
(ax )y = ey log a = ey log(e )
= ey(x log a) = exy log a = axy .
x

iv.
a1 = e1 log a = elog a = a.

v.
ax+y = e(x+y) log a = ex log a+y log a = ex log a · ey log a = ax · ab .

The function loga is the inverse function of ax . It can also be expressed in terms of log as follows. If
y = loga x, then x = ay = ey log a . So log x = y log a, and

log x
y= .
log a

4
It follows that
1
(loga x)′ = .
x log a
Let a in R. Define f : (0, ∞) → R by

f (x) = xa for every x > 0.

Then
f ′ (x) = axa−1 for every x > 0.

Proof: Write
f (x) = xa = ea log x ,
then
a a log x a
f ′ (x) = ·e = · xa = axa−1 .
x x

Exercise: If f is differentiable and


f ′ (x) = f (x) for all x,
then there is a number c such that
f (x) = cex for all x.

Solution: Let
f (x)
g(x) = .
ex
Then
ex f ′ (x) − f (x)ex
g ′ (x) = = 0.
ex
Hence there is a number c such that
f (x)
g(x) = = c.
ex

Reference

Michael Spivak, Calculus, W.A. Benjamin, Menlo Park, 1967.